Dirāsah Tahlīliyah ‘an al-Asmā’ al-Khamsah fī Sūrah Yūsuf - Ulum, Fatkhul; Rahman, Amri; Kudus, Ruhul; Hafid, Muh. Nur Ilham (Universitas Muhammadiyah Gorontalo, 2023)
This research aims to know the five names in Surat Yusuf, classify them, and explain their parsing. This research is a desk research that relies on books, publications and scientific journals related to the subject. The type of this research is analytical descriptive research based on the analysis and characterization of the content. There are three ways to analyze data: it begins with identifying the data, then classifying it, and finally presenting the data. After collecting and analyzing the data, the following results emerged: The five names are the names limited to (Akhu - Abu - Fu - Hamu - Dhu). Its ruling is of two types. The first is the five nouns that meet the conditions, so they are nominative with the waw on behalf of the ḍamma, the accusative is with the alif on the behalf of the fatḥa, and it is genitive with the yā’ on the behalf of the kasra, and the second is the five nouns that do not meet the conditions, so they are pronounced with the vowel. The five names that are found in Surat Yusuf are (Abu - Akhu - Dhu), but (Fu - Hamu) are not found in this Surah. The number of verses in Surat Yusuf, which includes the five names, is thirty-two (32) verses, and the number of its words is forty-seven (47) words, and they are as follows: The word (father) is mentioned twenty-seven (27) times, and the word (brother) is mentioned eighteen (18) times. Times, and the word (dhaw) twice. In terms of syntax, there are three sections: The first section is in the nominative case, and its nominative sign is the waw and the damma. The waw is found in four (4) words, and the damma is found in five (5) words. The second part is in the accusative case with three signs The alif, the fatha, and the yā’, so the alif is in fourteen (14) words, the fatha is in one (1) word, and the ya’ is in two (2) words. The third section is in the genitive case with two signs: The yā’ and the kasra, the yā’ is in twenty-one (21) words, and the kasra is in six (6) words.